Hypothetical learning trajectory trigonometry based on problem-based learning with Jambi Malay ethnomathematics nuances - Hamdani, Vikri; Armiati, Armiati; Arnawa, I Made; Jamaan, Elita Zusti (Al-Jabar: Jurnal Pendidikan Matematika, 2023)
Background: Trigonometry is a challenging subject for many high school students. Incorporating cultural relevance, such as Jambi Malay ethnomathematics, into teaching can be a way to facilitate understanding. This study focuses on developing a hypothetical learning trajectory (HLT) tailored to Class X high school students on the topic of trigonometry.Aim: The primary goal of this research is to create a valid, practical, and effective HLT for trigonometry based on problem-based learning, integrating the nuances of Jambi Malay culture.Method: This study employed a combination of two design research models: the Plomp model and the Gravemeijer and Cobb model. The research was conducted in three stages: 1) initial investigation, 2) product development, and 3) assessment. Expert validation and practical testing were carried out to assess the quality of the HLT.Result: Validation by experts indicated that the developed HLT achieved a score of 3.69, falling into the "very valid" category. Practicality testing revealed a score of 80.14, categorizing it as practical. Moreover, the HLT proved effective in enhancing students' mathematical communication skills.Conclusion: The developed Trigonometry HLT based on problem-based learning and integrated with Jambi Malay ethnomathematics is valid, practical, and effective. It not only adheres to quality benchmarks but also significantly improves students' mathematical communication abilities. Therefore, it fulfills the criteria for being a suitable and effective teaching approach.